2020
DOI: 10.9734/acri/2020/v20i430191
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of COVID-19 Safety Guidelines in Building Construction Sites in Anambra State, Nigeria

Abstract: Aim: The study evaluates how COVID-19 safety rules were applied in construction sites in Anambra state, Nigeria. Study Design: The study being a survey research was effected through literature review, a well-structured questionnaire and interview. Place and Duration of the Study: The study was conducted in Anambra State, Nigeria for a period of 6 months. Methodology: Being a survey research, questionnaire containing information relating to COVID-19 guidelines were randomly administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…For instance, some interviewees criticized that the implementation of anti-epidemic measures increased costs (Participants 4D, 6F, 10I, 14L) and the workload of site personnel (Participants 17N, 20O). Findings agreed with Ezeokoli et al [ 62 ] that enforcing these guidelines to the construction sites could induce extra costs to the project and might disrupt the normal site operations. Some workers even did not strictly follow the COVID-19 rules (Participant 17N).…”
Section: Resultssupporting
confidence: 87%
“…For instance, some interviewees criticized that the implementation of anti-epidemic measures increased costs (Participants 4D, 6F, 10I, 14L) and the workload of site personnel (Participants 17N, 20O). Findings agreed with Ezeokoli et al [ 62 ] that enforcing these guidelines to the construction sites could induce extra costs to the project and might disrupt the normal site operations. Some workers even did not strictly follow the COVID-19 rules (Participant 17N).…”
Section: Resultssupporting
confidence: 87%
“…Afkhamiaghda and Elwakil (2020) investigated the preliminary indexes that can help spread the virus in the construction industry, found that the volume of work, the job site location and the worker's daily activities can speedily spread the virus. Ezeokoli et al (2020), while investigating the application of Covid-19 safety rules amongst construction workers in construction sites, affirmed that maintaining stay-at-home policy when sick, using face-shields, placing hand sanitisers and wash hand basins in different and strategic locations are essential on construction sites. They revealed that maintaining a daily attendance log for staff and visitors and using personal protective equipment are common measures to Covid-19 safety guidelines on construction sites.…”
Section: Measures Required To Minimise the Spread Of The Virus On Construction Sitementioning
confidence: 99%
“…Also, Pan American Health Organisation (PAHO) and the United Nations Office for Project Services (UNOPS) (2020) came up with prevention measures for managing Covid-19 risks on construction sites to avoid the spread of the coronavirus. These guidelines were also emphasised in the studies of Ezeokoli et al (2020) and Wong et al (2020), as that which needs to be practiced on construction sites to minimise the spread of the diseases and promote health and safety, including but not limited to: Social distancing should be practiced. This could be achieved by maintaining 6-feet apart physical/social distancing between people.…”
Section: Measures Required To Minimise the Spread Of The Virus On Construction Sitementioning
confidence: 99%
See 2 more Smart Citations